Potential Application of MicroRNA Profiling to the Diagnosis and Prognosis of HIV-1 Infection - Su, Bin; Fu, Yuping; Liu, Yan; Wu, Haoquan; Ma, Ping; Zeng, Weiping; Zhang, Tong; Lian, Shi; Wu, Hao (Frontiers in Microbiology, 2018)
microRNAs (miRNAs) were first identified in Caenorhabditis briggsae and later recognized as playing pivotal roles in a vast range of cellular activities. It has been shown that miRNAs are an important mechanism not only for host defense against virus but also for the establishment of viral infection. During human immunodeficiency virus type 1 (HIV-1) infection, host miRNA profiles are altered either as a host response against the virus or alternatively as a mechanism for the virus to facilitate viral replication and infection or to maintain latency. The altered miRNA profiles can be detected and quantified by various advanced assays, and potentially serve as more sensitive, accurate and cost-efficient biomarkers for HIV-1 diagnosis and disease progression than those detected by currently available standard clinical assays. Such new biomarkers are critical for optimizing treatment regimens. In this review, we focus on the potential application of miRNA profiling to the diagnosis of HIV-1 infection and the monitoring of disease progression.